2017
DOI: 10.3390/su9101727
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Sustainable Development of an Economic-Energy-Environment (3E) System Based on System Dynamics (SD): A Case Study of the Beijing-Tianjin-Hebei Region in China

Abstract: Abstract:The sustainable development of an economic-energy-environment (3E) system has received increasing attention by the government because it both determines national development and individuals' health at the macro and micro level. In this paper, we synthetically consider various important factors based on analysis of the existing literature and use system dynamics (SD) to establish models of sustainable development of a 3E system. The model not only clearly shows the complex logical relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In recent years, some researches also confirmed the above findings (Finkelman & Tian, 2018;Sun, Wang, Wei, Li, & Liu, 2016). In order to achieve sustainable development of 3E system, it must be enforced to change coal-based energy consumption structure (Zuo, Shi, & Zhang, 2017). Due to the efforts in recent years, especially implementation of China's "Air Pollution Prevention and Control Action Plan" and implementation of ultra-low emission standards for atmospheric pollutants, environmental system has been significantly improved.…”
Section: The Evaluation Of 3e Systemmentioning
confidence: 81%
“…In recent years, some researches also confirmed the above findings (Finkelman & Tian, 2018;Sun, Wang, Wei, Li, & Liu, 2016). In order to achieve sustainable development of 3E system, it must be enforced to change coal-based energy consumption structure (Zuo, Shi, & Zhang, 2017). Due to the efforts in recent years, especially implementation of China's "Air Pollution Prevention and Control Action Plan" and implementation of ultra-low emission standards for atmospheric pollutants, environmental system has been significantly improved.…”
Section: The Evaluation Of 3e Systemmentioning
confidence: 81%
“…Kun et al used the coupling coordination index to evaluate the coordination between regional water and soil resources and ecological environment systems [30]. In the study of the coordination between economy and environment with the coupling model, many scholars further put forward that the coordinated development between economy and environment is a necessary condition for achieving sustainable development [31][32][33][34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…SD can be used to predict the economic benefits generated in the future [33][34][35][36], as well as analyze the key factors influencing the system [37][38][39]. Zuo et al [40] established a sustainable development model called the 3E system (economic-energy-environment System) by using the SD. The results showed that the long-term development of the 3E system in the Beijing-Tianjin-Hebei region was not sustainable, but it can be changed by adjusting the energy structure and increasing the investment in environmental protection, so as to improve the environmental quality.…”
Section: Literature Reviewmentioning
confidence: 99%